Avatar and distance simulation as a learning tool – virtual simulation technology as a facilitator or barrier? A questionnaire-based study on behalf of Netzwerk Kindersimulation e.V. - Löllgen, Ruth M.; Berger-Estilita, Joana; Rössler, Lisa A.; Mileder, Lukas P. (Frontiers in Pediatrics, 2022)
Background Virtual simulation modalities have been implemented widely since the onset of the severe acute respiratory syndrome coronavirus 2 pandemic restrictions in March 2020, as educators face persistent restrictions to face-to-face education of medical students and healthcare professionals. There is paucity of published data regarding the benefits and barriers of distance and avatar simulation training modalities. Methods We conducted a multicenter Central European survey to explore the advantages and challenges of avatar and distance simulation among participants of the inaugural virtual simulation competition, facilitated by Netzwerk Kindersimulation e.V., using a modified Delphi approach. Results Respondents indicated both a high overall satisfaction median 5.0 (Q25-Q75 4.0-6.0) out of 7 for avatar and distance simulation 6.0 (5.0-6.0), respectively, as well as a high achieved psychological safety with both simulation types 5.0 (4.0-6.0) versus 5.0 (4.0-6.0). The most frequently reported profits of avatar and distance simulation included the elimination of travel distances, associated lower costs, less time spent attending the education activity, and effective communication and leadership training, especially with avatar simulation. Most often named challenges were technical problems, limited reception of non-verbal cues and a spatial distance from the team/educator. Discussion Based on the results of this pilot study, avatar and distance simulation are valid alternatives to face-to-face simulation. Future studies are warranted to further explore the effectiveness of various types of virtual simulation compared to conventional presential simulation. We suggest using avatar-based simulation for targeted communication and leadership skills training and the application of distance simulation to bring simulation experts virtually to remote places where educator resources are lacking.